(untitled) (Environment & Health, 2017)
Background: The emergence of the new fabrics and widening of the assortment of children’s clothes needs the improvement of the methodological approaches and widening of the list of the indicators using for the hygienic assessment of textile products. Both the investigations of the qualities of goods and obtaining of the objective information from the customers about the most significant issues regarding the choice and exploitation of children’s goods play an important role in the solution of the wide spectrum of the tasks connected with the formation of the complex of the indicators for hygienic assessment of nonfood items. Objective: We determined the main factors affecting a choice of the parents of the children’s clothes of different functional purposes and the duration of the use of every layer of children’s clothes throughout the day. Materials and methods: We performed the questionnaire survey of the parents of 180 children aged 1-17 years. The analysis of the results was carried out taking into account the age periodization of children’s development. The results were calculated in Excel electronic tables with the help of the methods of variation statistics. Results: Performed questionnaire survey shows that over two- third of interviewed parents buy the children’s clothes more than 4 times a year. The majority of the parents buy clothes in the hypermarkets and the stores with specialized departments. At the same time 41.67 % of the families buy clothes in the Internet-shops and 45.00 % of the children wear clothes bought from private persons at the market. More than two-third of parents prefer domestic manufacturer of children’s clothes. The majority of the respondents regard the synthetic fibers in the first layer of children’s clothes negatively. The main factors affecting the choice of the parents, when buying clothes, were quality, outward, safety for health, fabric structure and price. The average duration of the wearing of the first layer of clothes makes up 7.22 -10.45 hours in a day. And duration of the wearing of the first layer of clothes by the children is authentically longer in comparison with the duration of wearing of the second layer of clothes (on the average by 1.5 fold) and in comparison with duration of wearing of the third layer of clothes(on the average by 2.7 fold).